The Suprachiasmatic Nucleus and the Intergeniculate Leaflet of the Flat-Faced Fruit-Eating Bat (Artibeus planirostris): Retinal Projections and Neurochemical Anatomy - Santana, Nelyane N. M.; Barros, Marília A. S.; Medeiros, Helder H. A.; Santana, Melquisedec A. D.; Silva, Lara L.; Morais, Paulo L. A. G.; Ladd, Fernando V. L.; Cavalcante, Jeferson S.; Lima, Ruthnaldo R. M.; Cavalcante, Judney C.; Costa, Miriam S. M. O.; Engelberth, Rovena C. J. G.; et al. (Frontiers in Neuroanatomy, 2018)
In mammals, the suprachiasmatic nucleus (SCN) and the intergeniculate leaflet (IGL) are the main components of the circadian timing system. The SCN, classically known as the master circadian clock, generates rhythms and synchronizes them to environmental cues. The IGL is a key structure that modulates SCN activity. Strategies on the use of time by animals can provide important clues about how some species are adapted to competitive process in nature. Few studies have provided information about temporal niche in bats with special attention on the neural substrate underlies circadian rhythms. The aim of this study was to investigate these circadian centers with respect to their cytoarchitecture, chemical content and retinal projections in the flat-faced fruit-eating bat (Artibeus planirostris), a chiropteran endemic to South America. Unlike other species of phyllostomid bats, the flat-faced fruit-eating bat’s peak of activity occurs five hours after sunset. This raises several questions about the structure and function of the SCN and IGL in this species. We carried out a mapping of the retinal projections and cytoarchitectural study of the nuclei using qualitative and quantitative approaches. Based on relative optical density findings, the SCN and IGL of the flat-faced fruit-eating bat receive bilaterally symmetric retinal innervation. The SCN contains vasopressin (VP) and vasoactive intestinal polypeptide (VIP) neurons with neuropeptide Y (NPY), serotonin (5-HT) and glutamic acid decarboxylase (GAD) immunopositive fibers/terminals and is marked by intense glial fibrillary acidic protein (GFAP) immunoreactivity. The IGL contains NPY perikarya as well as GAD and 5-HT immunopositive terminals and is characterized by dense GFAP immunostaining. In addition, stereological tools were combined with Nissl stained sections to estimate the volumes of the circadian centers. Taken together, the present results in the flat-faced fruit-eating bat reveal some differences compared to other bat species which might explain the divergence in the hourly activity among bats in order to reduce the competitive potential and resource partitioning in nature.